Generated datasets from dynamic reproduction of projectiles in ballistic environments for advanced research (DROPBEAR) testbed. (1st December 2022) - Nelson, Matthew; Laflamme, Simon; Hu, Chao; Moura, Adriane G; Hong, Jonathan; Downey, Austin; Lander, Peter; Wang, Yang; Blasch, Erik; Dodson, Jacob
Abstract: High-rate dynamics occur when a system's acceleration is larger than 100 gn over durations less than 100 ms. Structural health monitoring algorithms must be created for high-rate dynamic systems to maximize safety and minimize economic losses. There is a need to evaluate these algorithms for precision and accuracy prior to real-world implementation. An experimental testbed was created to simulate large-magnitude events while maintaining repeatability to accurately and robustly assess various structural health monitoring algorithms' capability to monitor high-rate dynamic systems. All previous datasets created on the experimental testbed are discussed, examining various sensor setups, excitations, and boundary condition changes to properly simulate near-high-rate events and provide robust experimental data to evaluate structural health monitoring algorithms.